Homogeneously aligned liquid crystal molecules on unidirectional buckle pattern of polyurethane films. Issue 1 (2nd January 2018) - Jeong, Hae-Chang; Won, Jonghoon; Lee, Ju Hwan; Mun, Hyo-Young; Kim, Dong Hyun; Lee, Dong Wook; Oh, Byeong-Yun; Han, Jeong-Min; Seo, Dae-Shik
ABSTRACT: We present the fabrication of an anisotropic structure on a polyurethane (PU) film for aligning liquid crystal (LC) molecules with ion beam (IB) irradiation at an incident angle. The obtained anisotropic structure assembles the LC cells in a layer that aligns LC molecules uniformly. Polarised optical microscopy images of an LC cell fabricated with IB-irradiated PU were captured to confirm the LC alignment state and compared with those fabricated with non-treated PU. To analyse the effects of the IB irradiation, X-ray photoelectron spectroscopy and field-emission scanning electron microscopy were used to investigate the chemical and morphological modifications, respectively. IB irradiation modifies the chemical structure of PU, which indicates that a new skin layer is formed on the PU films. This skin layer generates an in-plane compressive strain, thereby creating buckles on the PU films. Simultaneously, the physical collision of the reactive Ar + ions during IB irradiation induces a directional strain on the surface, thereby forming a unidirectional structure of buckles along the direction of IB irradiation. The PU film annealed at 200°C showed the high average transmittance of 88.9%, which is appropriate as an alignment layer. Graphical Abstract: